2018
DOI: 10.3390/app8050742
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Assistants—An Analysis and Future Trends Based on Speculative Default Reasoning

Abstract: Abstract:Once a person is diagnosed (or a caregiver suspects that the person may have) cognitive disabilities he may lose the state of being autonomous, which may range from partial to total loss of independence, according to the level of incidence. Smart houses may be used as a tentative solution to overcome this situation. However, when one goes outside their premises, this alternative may become unusable. Indeed, due to the decreased orientation ability, caregivers may prevent these people from going out, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Finally, the third work [24] presented CogHelper, which is an orientation system for people with cognitive disabilities. The main idea is that using this system, people with cognitive disabilities may have a more active life, reducing the worry of getting lost both indoors and outdoors.…”
Section: Mas In Ambient Intelligencementioning
confidence: 99%
“…Finally, the third work [24] presented CogHelper, which is an orientation system for people with cognitive disabilities. The main idea is that using this system, people with cognitive disabilities may have a more active life, reducing the worry of getting lost both indoors and outdoors.…”
Section: Mas In Ambient Intelligencementioning
confidence: 99%
“…In [22] the authors develop a personal assistant agent leveraging and complementing ambient intelligence systems to safely navigate people with cognitive disabilities in unfamiliar environments. The proposed system features location tracking, an orientation system, and speculative reasoning to enable monitoring of patients' locations by caregivers and relatives, increase autonomy of patients, and pro-actively detect potential mistakes leading to the patient getting lost.…”
Section: Socio-technical Systemsmentioning
confidence: 99%
“…We believe these three areas of artificial intelligence are essential to define a personalized approach to correctly support elderly people and motivate them to pursuit healthier lifestyle habits. For this, cognitive assistants can provide tools and features to help people perform activities of daily living [14]. Furthermore, these assistants will interact directly with the user using different mechanisms such as affective wearables to collect physiological data and correctly assess user's affective states and gamification to motivate the user to perform different activities and improve health condition.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, the authors also concluded that the developed system should never replace the caregiver but act as a complementary to the work of the caregivers instead. Ramos et al [14] proposed a system using a smartphone and augmented reality to guide people with mild or moderate cognitive disabilities according to their preferences and offers an application that allows the caregiver to locate the disabled person. The developed system also considered ethical questions since it collects and ciphers sensitive data and assumes the disabled person has given his/her consent to provide all the information necessary for the system to operate correctly.…”
Section: Cognitive Assistantsmentioning
confidence: 99%